Effective role of medium supplementation in microalgal lipid accumulation. Issue 5 (13th February 2018) - Fazeli Danesh, Azadeh; Mooij, Peter; Ebrahimi, Sirous; Kleerebezem, Robbert; van Loosdrecht, Mark
Abstract: The present study investigated the interaction between starch and lipid accumulation in a green microalgae enrichment culture. The objective was to optimize the lipid content by manipulation of the medium in regular batch culture. Two medium designs were evaluated: First a high ortho‐P concentration with vitamin supplementary (Pi‐vitamins supplemented medium), second normal growth medium (control). Both media contained a low amount of nitrogen which was consumed during batch growth in three days. The batch experiments continued for another 4 days with the absence of soluble nitrogen in the medium. When the mixed microalgal culture was incubated in the Pi‐vitamin supplemented medium, the lipid, and starch content of the culture increased within the first 3 days to 102.0 ± 5.2 mg/L (12.7 ± 0.6% of DW) and 31.7 ± 1.6 mg/L (4.0 ± 0.2% of DW), respectively. On the last day of the experiment, the lipid, and starch content in Pi‐vitamin medium increased to 663.1 ± 32.5 mg/L (33.4 ± 1.6% of DW) and 127.5 ± 5.2 mg/L (6.4 ± 0.3% of DW). However, the lipid and starch content in the control process, reached to 334.7 ± 16.4 mg/L (20.1 ± 1.0% of DW) and 94.3 ± 4.6 mg/L (5.7 ± 0.3% of DW), respectively. The high Pi‐vitamin medium induced storing lipid formation clearly while the starch formation was not affected. The lipid contents reported here are among the high reported in the literature, note that already under full growth conditions significant lipid levels occurred in the algal enrichment culture. The high lipid productivity of the reported mixed microalgae culture provides an efficient route for efficient algal biodiesel production. Abstract : The interaction between starch and lipid accumulation was investigated in a green microalgae enrichment culture. Two medium designs were evaluated: First a high ortho‐P concentration with vitamin supplement (Pi‐vitamins supplemented medium), second normal growth medium (control). The high Pi‐vitamin medium clearly induced storing lipid formation while the starch accumulation was not affected. Since the starch content was identical for both treatment, orthophosphate did not act as an AGPase enzyme inhibitor in the microalgal community. This study shows a strong stimulating effect of vitamin addition on lipid production.